Thermal effects on the synthesis of acetals in a simulated moving bed adsorptive reactor - Graça, Nuno S. (2014)
The effect of temperature on simulated moving bed adsorptive reactor performance was studied by simulation with both isothermal and non-isothermal mathematical models. Simulated results with isothermal mathematical model showed an improvement of SMBR performance criteria and the increase on reaction/separation regions with temperature. It was shown by simulations with non-isothermal mathematical model that the SMBR performance can be also improved by using the adiabatic operation mode. This study of the thermal effects on SMBR operation is an important step for a further implementation of energy integration concepts such as autothermal operation.